TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN TERPADU SATU PINTU DI PENGADILAN NEGERI SURABAYA KELAS 1A KHUSUS - Baitty Aqilatun Nufus; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2026)
One Stop Integrated Service (PTSP) is a public service innovation aimed at improving effectiveness transparency and public satisfaction in judicial administrative services. The Surabaya District Court Class 1A Special as a judicial institution with a high caseload and complex service demands is required to implement PTSP optimally and oriented toward service user satisfaction. This study aims to analyze the level of public satisfaction with PTSP services at the Surabaya District Court Class 1A Special based on the Community Satisfaction Survey (SKM) indicators in accordance with the Regulation of the Minister of Administrative and Bureaucratic Reform Number 14 of 2017. This research employed a descriptive quantitative method with data collected through questionnaires distributed to PTSP service users and supported by observation and documentation. Satisfaction measurement was conducted across nine service elements and analyzed using the Community Satisfaction Index (IKM). The results show that the level of public satisfaction with PTSP services falls within the good category with an IKM score of 3.225 or a converted value of 81.35. Facilities and infrastructure obtained the highest score while service completion time received the lowest score. These findings indicate that PTSP services have generally been implemented in accordance with service standards but still require improvement particularly in service completion timeliness and optimization of information delivery to the public.